(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the characteristics of symbols actively used in color vocabulary, as well as the properties and possibilities for expressing the symbolic meaning of words denoting color. Information on the regional localization of this type of symbol is provided.